Evaluation of the Cost and Benefits of Halal Certificates for Manufacturing MSMEs: A Literature Study - Rochmatullah, Mahameru Rosy; Aji, Nur Prasetyo; Tulaila, Rohmah; Asyiqin, Zainal (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Awareness of the importance of halal in a product, not only in the raw materials and production process, but also in the underlying financial aspects of the product. This research is about changes in the cost structure experienced by producers before and after obtaining halal certificates, as well as identifying the factors that affect it.this research is based on the literature Review approach, by analyzing previous research data and data obtained from BPJPH. The results of the study show that halal certificates are able to significantly change the company's cost structure, including preparation, implementation, and maintenance costs. Factors influencing such changes in the cost structure include the scale of operations, product complexity, internal readiness, state regulations, and market competition. This research provides insights for producers and stakeholders in understanding the economic implications of halal certification.